1999
DOI: 10.1086/306773
|View full text |Cite
|
Sign up to set email alerts
|

The Host Galaxy of the Broad Absorption Line QSO PG 1700+518 and Its Ring Galaxy Companion: NICMOS 1.6 Micron Imaging

Abstract: The 1.6 km Near Infrared Camera and Multiobject Spectrometer image of the broad absorption line QSO PG 1700]518 clearly resolves the QSO host galaxy and a ringlike companion. The companion is most likely a ring galaxy produced in a collision with the QSO galaxy D5 ] 107 yr ago. The morphology of the PG 1700]518 system is very similar to IRAS 04505 [2958[ (Boyce et al. 1996. Both objects were identiÐed in a sample of eight QSOs selected by "" warm ÏÏ far-IR colors and extreme IR luminosities (Low et al. 1988). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 31 publications
5
26
2
Order By: Relevance
“…Recently, high resolution images of these IR selected BAL QSOs show in practically "all of these objects" the presence of arcs/shells (Boyce et al 1997;Stockton, Canalizo, & Close 1998;Surace et al 1998;Hines et al 1999); and they are very similar to those -60observed in Mrk 231 (the nearest merger+IR+GW+Fe ii+BAL galaxy/QSO; see Lipari et al 1994) and in Arp 220 (the nearest merger+IR+GW galaxy; see Heckman et al 1987).…”
Section: Bal+feii Qsos and Formation/evolution Of Galaxiesmentioning
confidence: 64%
“…Recently, high resolution images of these IR selected BAL QSOs show in practically "all of these objects" the presence of arcs/shells (Boyce et al 1997;Stockton, Canalizo, & Close 1998;Surace et al 1998;Hines et al 1999); and they are very similar to those -60observed in Mrk 231 (the nearest merger+IR+GW+Fe ii+BAL galaxy/QSO; see Lipari et al 1994) and in Arp 220 (the nearest merger+IR+GW galaxy; see Heckman et al 1987).…”
Section: Bal+feii Qsos and Formation/evolution Of Galaxiesmentioning
confidence: 64%
“…Quasar 1700+518 is a bright BAL quasar of low redshift . Such low‐redshift BAL objects are rare and hard to discover, since the broad absorption lines are in the ultraviolet, and consequently quasar 1700+518 has received much interest: specific studies of this quasar have been undertaken in many different wavebands (Hutchings, Neff & Gower 1992; Stockton, Canalizo & Close 1998; Hines et al 1999). Because of the low redshift and the brightness of the quasar, 1700+518 has also been included in many samples of quasars imaged to obtain details of their host galaxies (Neugebauer et al 1985; McLeod & Rieke 1994b), although these have only provided upper limits for the host magnitude.…”
Section: Results Of the Analysismentioning
confidence: 99%
“…Because of the low redshift and the brightness of the quasar, 1700+518 has also been included in many samples of quasars imaged to obtain details of their host galaxies (Neugebauer et al 1985; McLeod & Rieke 1994b), although these have only provided upper limits for the host magnitude. More recent imaging studies have shown that the morphology of the underlying structure consists of a disturbed host predominantly to the south‐west of the core (Stockton et al 1998) and a close interacting companion to the north‐east (Hutchings et al 1992) which is most likely a ring galaxy (Hines et al 1999). Deconvolution of the light from this quasar, as shown in Fig.…”
Section: Results Of the Analysismentioning
confidence: 99%
“…At first, the issue of co-evolution could be studied in phenomenology. In fact, there are many observations of both imaging and spectroscopy that show the evidence of co-existence of AGN and circumnuclear star formation (e.g., Canalizo & Stockton 2001;Cid Fernandes et al 2001Hines et al 1999;Schinerer et al 1998;Heckman et al 1997;Gonzalez Delgado 2002;Zuther et al 2007;Sarzi et al 2007;Asari et al 2007;Davies et al 2007).…”
Section: Composite Galaxiesmentioning
confidence: 99%